2018
DOI: 10.31887/dcns.2018.20.1/whauser
|View full text |Cite
|
Sign up to set email alerts
|

Facts and myths pertaining to fibromyalgia

Abstract: Fibromyalgia (FM) is characterized by chronic widespread pain, unrefreshing sleep, physical exhaustion, and cognitive difficulties. It occurs in all populations throughout the world, with prevalence between 2% and 4% in general populations. Definition, pathogenesis, diagnosis, and treatment of FM remain points of contention, with some even contesting its existence. The various classification systems according to pain medicine, psychiatry, and neurology (pain disease; persistent somatoform pain disorder; masked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 62 publications
(60 reference statements)
0
65
0
3
Order By: Relevance
“…The average global prevalence of FM is 2.4%, with notable variations by country; from 0.4% in Greece to 9.3% in Tunisia [ 3 ]. FM can affect any age and the female-to-male ratio is 8–10:1 [ 4 ], although most are women between 40 and 60 years old [ 5 ]. In addition, fibromyalgia syndrome is associated with a significant burden on the individual and society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The average global prevalence of FM is 2.4%, with notable variations by country; from 0.4% in Greece to 9.3% in Tunisia [ 3 ]. FM can affect any age and the female-to-male ratio is 8–10:1 [ 4 ], although most are women between 40 and 60 years old [ 5 ]. In addition, fibromyalgia syndrome is associated with a significant burden on the individual and society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known the frequent functional and psychiatry comorbidities in fibromyalgia that can negatively affect the patients' mood [ 16 , 17 ]. Additionally, they are a particular population with low access to healthcare and constant debilitating pain and fatigue decreasing their quality of life [ 59 , 60 ]. Therefore, the emotional support in these patients could increase the resilience and adaptation to the disease and facilitate the seek for novel therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were excluded from the study as it could not be concluded whether they had psychogenic or non-psychogenic conditions as of March 2020. [ 10 11 12 13 ] Besides, three middle-aged female patients who were eventually diagnosed with the postmenopausal syndrome were also excluded from this study because of the difficulty of objectively diagnosing the disorder solely based on laboratory and physiological diagnostic examinations. [ 14 ] Consequently, the remaining 277 patients with persistent physical symptoms were considered eligible for the study.…”
Section: Methodsmentioning
confidence: 99%